Berberine in the Medicinal Plant of Tali kuning (Tinospora dissitiflora Diels) - Wahyudi Wahyudi; Y. Ohtani; H. Ichiura (Masyarakat Peneliti Kayu Indonesia, 2011)
Two different approaches have been used to determine the bioactive compounds in the medicinal plant of Tali kuning (Tinospora dissitiflora Diels). Firstly, the conventional approach using column chromatography (CC), and preparative thin layer chromatography (PLC) eluted with benzene:ethyl acetate: formic acid (5:4:1, and 5:4:2, respectively), followed by CC eluted with benzene:methanol (3:2) were used to separate and isolate berberine from the chloroform fraction of Tali kuning. Structural elucidations of the isolated compounds were conducted using nuclear magnetic resonance (NMR) and mass spectrometry (MS). Secondly, a rapid and simple approach use the integrated intensities of proton signals for H-13 and H-8 of berberine on 1H-NMR spectra, then the qualitative and quantitative determination of berberine in Tali kuning can be achieved directly from the crude extracts using 1H-NMR. The proton signals for H-13 and H-8 of berberine on 1H-NMR spectra, which appeared at empty regions as singlet, and without interference from the other signals, were available for qualitative determination of berberine. Whereas, the integrated intensity of proton signal for H-13 on 1H-NMR spectrum was used for quantitative determination of berberine. Berberine content of Tali kuning was calculated manually based on the integrated intensity of proton H-13 from the authentic berberine chloride, which was 18.6 mg/g based on the weight of air-dried wood meal. This berberine content was comparable to that (22.78 mg/g) of Amur corktree (Phellodendron amurense Rupr), which is widely acknowledged for good producer of berberine.